Progesterone administration reduces the number of hypertrophic microglia/macrophages and modulates the expression profile of M1/M2 markers and inflammasome components after acute experimental spinal cord injury - Raggio, María Celeste (2021)
Neuroinflammation is a hallmark of central nervous system pathologies, including spinal cord injury (SCI). In particular, the acute activation of macrophages and resident microglia are critically implicated in the detrimental long-standing consequences of spinal trauma, such as the onset and maintenance of neuropathic pain [5]. Indeed, the fine-tuning of microglia/macrophage polarization from classically-activated (M1, inflammatory) towards alternatively-activated (M2, anti-inflammatory) states represents an active research focus of restorative strategies in a wide range of experimental nervous system trauma, including SCI [1], and may offer a therapeutic opportunity to prevent the risk of developing pain later. We have previously shown that progesterone, a neuroactive steroid, exhibits neuroprotective and pro-myelinating actions in experimental spinal lesions [3, 6] and could stand as a promising repositioning molecule for timely targeting the harmful aspects of acute inflammation [2, 4], while preserving anti-inflammatory and pro-reparative features.